Quincy Jordan - Storer, Jen 1961- (Crystal Bay girls, 2014)
Quincy Jordan doesn't want to meet her hippie cousins and go to school in Crystal Bay. Her life in Sydney is perfect. She's going to save her parents' marriage, score perfect marks at school and become a surgeon. Her only regret is that she'll never be a fashion designer. But sacrifices must be made. There's no way that Quincy is going to be 'Crystallised' - that is until her cousin Esme, the school musical and a cute boy called Harris change everything